Green entrepreneurial self-efficacy and environmental performance of SMEs: Mediating and moderating role of green innovation and green purchase behaviour - Khutso Pitso Mankgele (Global Business & Finance Review (GBFR), 2023)
Purpose: The main purpose of this study is to investigates how green entrepreneurial self-efficacy (GESE) influences environmental performance (EP) in the Gauteng province: the mediating and moderating role of green innovation (GI) and green purchase behaviour (GPB). Design/methodology/approach: The study followed the quantitative research design and a self-administered questionnaire was employed during the data collection process. Data was collected from one hundred ninety-five SME owners in a cross-sectional survey. The participants of this study were in the retail, service and manufacturing sectors. The data was analysed using SmartPLS 4.0. Findings: The empirical findings of this study show that there is a significant positive relationship between GESE and the EP of SMEs. The study further shows that the relationship between GESE and EP is partially mediated by GI and the relationship is also moderated by GPB at an average weight. Research limitations/implications: The study has the following limitations and suggests some new study areas. First, the cross-sectional nature of the survey limits the ability to separate cause-and-effect relationships, and a longitudinal study will help to improve the results. Second, the survey was done on firms in one industry and one country. To improve the generalisability of the findings, further studies can include other industries in other countries. Originality/value: This paper fills a gap in the literature by exploring external business variables mediating and moderating the relationship between GESE and EP and contributes to the discussion on the contradictory results regarding the relationship between GESE and EP.
Keywords: 650; Entrepreneurship self-efficacy; Environmental performance; Green innovation; Green purchase behaviour; Small medium business